EUV Microscopy: A Unique Approach for Materials Characterization: Ultrafast extreme ultraviolet provides novel capability for probing nanoscale material characteristics. Issue 3 (24th May 2019) - Manser, Rosy
Abstract: Understanding of fundamental processes as well as nanostructure performance of nano‐engineered systems, novel materials, and quantum architectures, often requires advanced imaging and spectroscopic tools. This is particularly critical as dimensions shrink below 100 nm as visible light cannot directly probe function at these lengthscales. Ultrafast extreme ultraviolet (EUV) techniques offer a pathway to both functional characterization and imaging at sub‐50 nm lengthscales, and a host of use cases in materials and nano science have been demonstrated. Progress in terms of source and instrumentation development are assisting the rapid increase in the availability of these approaches in the laboratory.